Antioxidant and anti-inflammatory activity of constituents isolated from Dendrobium nobile (Lindl.) - Lei, Hui; Zou, Shunmei; Lin, Jiafu; Zhai, Longfei; Zhang, Yifeng; Fu, Xiujuan; Chen, Siwei; Niu, Hong; Liu, Feifei; Wu, Chunlian; Zhang, Dan (Frontiers in Chemistry, 2022)
Dendrobium nobile (Lindl.) have long been used as herbal tea and a traditional herbal medicine to treat Alzheimer’s disease (AD). In the current study, nineteen compounds (1-19), including two new vitamin E homologues (1-2), one new sesquiterpene (6), and two new dendrobines (7, 8), were isolated and identified from stems of Dendrobium nobile. Their structures were elucidated on the basis of NMR, calculated with electronic circular dichroism data analysis, and the antioxidant, anti-inflammatory, and anti-tumour activity of isolated compounds were evaluated. Among them, compound 2 demonstrated significant antioxidant activity compared with ascorbic acid (VC), while compounds 2 and 4 also exhibited an equal effect to positive control cisplatin. This study on the biological activity of the new vitamin E homologues from Dendrobium nobile may indicate its potential application in the pharmaceutical and food industries.